Case Investigation and Contact Tracing Efforts From Health Departments in the United States, November 2020 to December 2021 . (20th June 2022) - Stargel, Alison; Taylor, Melanie M; Zansky, Shelley; Spencer, Kimberly; Hogben, Matthew; Shultz, Alvin
Abstract: Background: Sixty-four state, local, and territorial health departments (HDs) in the United States report monthly performance metrics on coronavirus disease 2019 (COVID-19) case investigation and contact tracing (CI/CT) activities. We describe national CI/CT efforts from 25 October 2020 through 24 December 2021, which included 3 peaks in COVID-19 case reporting. Methods: Standardized CI/CT data elements submitted by the 64 HDs were summarized as monthly performance metrics for each HD and the nation. These included measures of CI/CT completeness, timeliness, and workloads. We calculated contact tracing efficacy as the proportion of new cases that occurred in persons identified as contacts within the 14 days before the case was reported. Results: A total of 44 309 796 COVID-19 cases were reported to HDs, with completed HD interviews in 18 153 353 (41%). Less than half of interviews yielded ≥1 contact. A total of 19 939 376 contacts were identified; 11 632 613 were notified (58%), with 3 618 846 undergoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing within 14 days of notification. Of the total reported cases, 2 559 383 occurred in recently identified contacts. Conclusions: We document the resource-intense nationwide effort by US HDs to mitigate the impact of COVID-19 through CI/CT before and after vaccines became widely available. These results document the coverage and performance of CI/CT despite case surges and fluctuating workforce and workloads.